2018
DOI: 10.1111/pim.12525
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human dendritic cell activity by Giardia and helminth antigens

Abstract: Giardia duodenalis is a common intestinal protozoan parasite known to modulate host immune responses, including dendritic cell (DC) function. Coinfections of intestinal pathogens are common, and thus, DCs may be concurrently exposed to antigens from multiple parasites. Here, we investigated the effects of G. duodenalis products on human monocyte-derived DC function independently and in combination with helminth antigens (Ascaris suum and Trichuris suis). All antigens individually induced an anti-inflammatory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
2
8
0
4
Order By: Relevance
“…58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation. 58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation. 58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have examined the immunomodulatory effects of helminth PCF on human moDCs reporting that helminth PCF conditioning suppresses pro-inflammatory cytokine production (IL-12p70, IL-6, IL-23 and TNF-a) in LPS-stimulated moDCs. 58,59 Our analysis of the early transcriptional profile of helminth PCF-treated LPS + IFN-c-matured moDCs supports these previous findings and suggests that helminth PCF may interfere with TLR4 signaling to exert its immunosuppressive effects, as indicated by identification of decreased expression of molecules downstream of TLR4 activation. Our results showed that helminth PCF down-regulated expression of genes encoding components of predominantly the MyD88-dependent but also the MyD88-independent TLR4 signaling cascade like IRAK2, 60 MAP3K8, 61 IFNB and IRF8.…”
Section: Discussionsupporting
confidence: 86%
“…Có nhiều yếu tố ảnh hưởng đến quá trình apoptosis của tế b o như phối tử toll-like receptor (TLR) và các loại cytokine viêm khác nhau (Simpson et al, 2016;Summan et al, 2018;Yoo et al, 2012). Một trong những phối tử TLR được nghiên cứu rộng rãi trên tế bào miễn dịch là phối tử TLR4 (lipopolysaccharide, LPS).…”
Section: Mở đầUunclassified
“…Một trong những phối tử TLR được nghiên cứu rộng rãi trên tế bào miễn dịch là phối tử TLR4 (lipopolysaccharide, LPS). Sự gắn kết giữa phối tử này và thụ thể TLR4 trong tế bào kích hoạt các tín hiệu phân tử hoạt động l m tăng tiết các cytokine như TNF- và INF và giảm tiết IL-10 (Zhang and Zheng, 2005), dẫn tới ức chế hoạt động apoptosis của tế bào (Summan and Nejsum, 2018). Khả năng tiết các cytokine gây viêm của tế bào liên quan trực tiếp đến hoạt động miễn dịch của cơ thể, từ đó điều hòa quá trình trả lời miễn dịch hoặc trả lời đối kháng hoặc dị ứng khi cơ thể tiếp xúc với các yếu tố gây bệnh hoặc các tác nhân khác từ m i trường sống (Banchereau et al, 2000;Elmore, 2007).…”
Section: Mở đầUunclassified
See 1 more Smart Citation